Evaluation of the safety of a genetically modified DAS-444Ø6-6 soybean meal and hulls in a 90-day dietary toxicity study in rats. (November 2017) - Papineni, Sabitha; Murray, Jennifer A.; Ricardo, Ekmay; Dunville, Christina M.; Sura, Radha Krishna; Thomas, Johnson
Abstract: A 90-day sub chronic toxicity study was conducted in rats to evaluate the safety of genetically modified DAS-444Ø6-6 soybeans expressing herbicide tolerant proteins when compared with its conventional comparators (non-transgenic near isoline control soybean and three commercially available non-transgenic line control soybeans). Rats were given diets formulated with either 10% or 20% w/w of soybean meal and 1% or 2% hulls of DAS-444Ø6-6 soybean with an equivalent amount of hulls from an isoline non-transgenic control soybean for at least 90 days. In addition, three separate 20% w/w non-transgenic commercially available soybean varieties were also given to groups of rats to serve as reference controls. Animals were evaluated by cage-side and hand-held detailed clinical observations, ophthalmic examinations, body weights/body weight gains, feed consumption, hematology, prothrombin time, urinalysis, clinical chemistry, selected organ weights, and gross and histopathologic examinations. Under the conditions of this study, the genetically modified DAS-444Ø6-6 diets did not cause any treatment-related effects in rats following 90 days of dietary administration as compared with rats fed diets with soybean of isoline control or commercial reference controls and are considered equivalent to the diets prepared from conventional comparators. Highlights: A 90-day dietary toxicity study in rats was conducted to evaluate the safety of DAS-444Ø6-6 soybeans. DAS-444Ø6-6 soybean diets did not produce any adverse effects in rats at any time during the study. Soybeans from DAS-444Ø6-6 are considered as safe and nutritious as the non-transgenic and conventional varieties.